A dimensão da autonomia na educação escolar indígena da aldeia Kaimbé - Ramos, Humberto Teixeira (2019)
This dissertation results from research on indigenous education, whose objective was toobserve the dimension of pedagogical autonomy in the development of indigenous school education offered at the Kaimbé do Massacará, Village School city of Euclides da Cunha- BA. The specific part of the field was carried out between the months of February and May 2019 was developed from understanding with the school, who collaborated with the research in all stages. To perform the data interpretation was adopted from the perspective of Critical Ethnography (MACEDO, 2000). The instruments of questionnaires and semi-structured interviews were used to develop a descriptive analysis of a qualitative approach that was developed based on a bibliographical review around the questions of historical nature of the community, as well as on the legislation of indigenous education and the training of indigenous teachers implemented in Brazil and Bahia. The participants represent three segments of the community: indigenous teachers, students and elders or leaders, who presented their perceptions about categories that maintain a strategic link with indigenous school education, such as autonomy, interculturality, historical awareness and relationship between school and work. One of the specific objectives was the observation about the influence of elements of the Intercultural Licenciatura in Indigenous School Education in the work of community teachers who are linked to this formation. The research aimed to establish a triangular relationship between the guidelines and determinations contained in the legislation pertinent to indigenous education, the execution of the school activity and the perceptions about school education contained in the interviews of the participants, highlighting intersections and dissentions between the orientations of theoretical and normative references and the performance of school activities regarding the relationship between students and the world surrounding them within and outside the community.